The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1124/jpet.108.146944
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic-Like Effect of Retigabine [N-(2-Amino-4-(fluorobenzylamino)-phenyl)carbamic Acid Ester], a KCNQ Potassium Channel Opener, via Modulation of Mesolimbic Dopaminergic Neurotransmission

Abstract: Dopaminergic (DAergic) neurons in the ventral tegmental area express both KCNQ2 and KCNQ4 channels, which opening is expected to decrease neuronal excitability via neuronal hyperpolarization. Because psychotic symptoms are believed to be associated with an increased excitability of dopamine (DA) cells in the mesencephalon, KCNQ channels might represent a new potential target for the treatment of psychosis. The aim of our study was to investigate the antipsychotic-like potential of KCNQ channel opening via modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
44
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 39 publications
9
44
1
Order By: Relevance
“…Moreover, the effects described at the 4 mg·kg -1 dose in the anxiety, rotarod and ethanol interaction tests are consistent with the profile of retigabine (Blackburn-Munro et al, 2005;Korsgaard et al, 2005). Recently, Damgaard et al (2011) have shown that AA29504 reverses recognition memory deficits in an animal model of schizophrenia, albeit retigabine is also effective in schizophrenia models (Sotty et al, 2009). …”
Section: In Vivo Propertiessupporting
confidence: 71%
“…Moreover, the effects described at the 4 mg·kg -1 dose in the anxiety, rotarod and ethanol interaction tests are consistent with the profile of retigabine (Blackburn-Munro et al, 2005;Korsgaard et al, 2005). Recently, Damgaard et al (2011) have shown that AA29504 reverses recognition memory deficits in an animal model of schizophrenia, albeit retigabine is also effective in schizophrenia models (Sotty et al, 2009). …”
Section: In Vivo Propertiessupporting
confidence: 71%
“…85 Ketamine induces aberrant firing of dopamine neurons. 86 Perhaps that firing underpins the preserved sensitivity to devaluation in the NHVL rats.…”
Section: Imagining Rats?mentioning
confidence: 99%
“…The concentration of dopamine in the dialysates was analysed by means of HPLC with electrochemical detection as previously described [26]. The monoamines were separated by reverse-phase liquid chromatography (ODS 150 9 3 mm).…”
Section: Methodsmentioning
confidence: 99%